Felice Giardini and Professional Music Culture in Mid-Eighteenth-Century London - Duncan, Cheryll (Milton : Routledge, 2019)
Felice Giardini and Professional Music Culture in Mid-Eighteenth-Century London explores Giardini's influence on British musical life through his multifaceted career as performer, teacher, composer, concert promoter and opera impresario. The crux of the study is a detailed account of Giardini's partnership with the music seller/publisher John Cox during the 1750s, presented using new biographical information which contextualizes their business dealings and subsequent disaccord. The resulting litigation, the details of which have only recently come to light, is explored here via a complex set of archival materials. The findings offer new information about the economics of professional music culture at the time, including detailed figures for performers' fees, the printing and binding of music scores, the charges arising from the administration of concerts and operas, the sale, hire and repair of various instruments and the cost of what today we would call intellectual property rights. This is a fascinating study for musicologists and followers of Giardini, as well as for readers with an interest in classical music, social history and legal history.
Chapter 4 Giardini and Cox in courtGiardini's indebtedness to Cox; The publication of Giardini's Overtures; Cox's administration of concerts and operas; Chapter 5 Giardini's account at Cox's music shop; Violin costs; Giardini's other instruments; Music purchases; Other expenses; Advertising costs; Giardini's picture; Conclusion; Appendix 1: Schedule A1; Appendix 2: Giardini's associates; Chabran (Schabran), Charles (1723-54); Ciampi (Chiampi), Vincenzo (?1719-62); Colla (Cola) brothers (fl. c.1740-c.1770); Mrs Ogle (c.1710-c.1765); Winch, Christopher (fl. c.1725-61); Index
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: MUSIC / Genres & Styles / Classical; Giardini, Felice, -- 1716-1796.; Music -- England -- London -- 18th century -- History and criticism; Concerts -- England -- London -- History -- 18th century